Management of common mental disorders should take place in primary health or specialized care? Clinical decisions of psychiatrists from Latin American countries - Haddad, Michel; Rojas Vistorte, Angel O.; Guerra Haddad, Glenda; Ribeiro, Wagner; Ziebold, Carolina; Asevedo, Elson; Evans-Lacko, Sara; Ulloa Guerra, Óscar; de Jesus Mari, Jair (PLoS ONE, 2023)
Objective The objective of our study was to explore clinical decisions of psychiatrists regarding the management of common mental disorders in primary care (PC) in four Latin Americans countries, through the application of clinical vignettes. Methods Using a cross-sectional design, we conducted a self-administered online questionnaire survey of psychiatrists from Bolivia, Brazil, Cuba, and Chile. The questionnaire covered sociodemographic and professional information. The psychiatrists’ clinical decisions were assessed through three clinical vignettes representing typical PC cases of depression, anxiety, and somatization. Results 230 psychiatrists completed the online survey. Psychiatrists from Brazil were less likely to recognize depression as a mental disorder than those from Cuba (odds ratio (OR) = 0.30, 95% confidence interval (CI), 0.10 to 0.91, p < 0.04). Female gender (OR = 0.19, 95% CI, 0.04 to 0.91, p < 0.02) and older age (OR = 0.92, 95% CI, 0.87 to 0.97, p < 0.01) reduced the likelihood of agreement that depression cases should be treated by a Primary Care Physician (PCP). In the somatoform symptoms vignette, longer training duration increased the likelihood of agreement that treatment should be done by a psychiatrist instead of a PCP (OR = 1.19, 95% CI, 1.04 to 1.37, p < 0.01). In the anxiety vignette, females (OR = 2.38, 95% CI, 1.10 to 5.13, p < 0.01) and participants from Bolivia (compared with Cubans, OR = 4.19, 95% CI, 1.22 to 14.42, p < 0.02) were more likely to consider that these patients should be treated by a psychiatrist instead of a PCP. Discussion Most psychiatrist respondents agreed that patients with depression should be treated by PCPs and that somatoform and anxiety cases should be treated by psychiatrists. These results show that psychiatrists consider that they, and not PCPs, should treat patients with common mental disorders, regardless of the evidence showing that common mental disorders can be treated by primary care physicians in PC.
Keywords: genera-practitioners; family physicians; services; depression; views; prevalence; strategies; GPS; JCR